The energy debate - Ezra, Derek (Croydon, Surrey: Benn Technical Books, 1983)
Energy policy has been the subject of debate in Britain for centuries; and the debate still goes on. So, it is the purpose of this book to set down the present state of the debate and to assess the extent to which there appears to be agreement.
Includes bibliographical references: p. 240-248 and index.
ne 20/04/2018
Loans
Keywords: Energy Conservation; Energy policy